Mitochondrial Homeostasis and Mast Cells in Experimental Hepatic Ischemia-Reperfusion Injury of Rats - Koc, Suleyman; Dogan, Halef Okan; Karatas, Ozhan; Erdogan, Mehmet Mustafa; Polat, Vural (Turkish Journal of Gastroenterology, 2022)
Background: Ischemia-reperfusion injury is a histopathological event and is an important cause of morbidity and mortality after hepatobiliary surgery. We aimed to investigate the protective effect of uridine on hepatic ischemia-reperfusion injury in rats. Methods: The animals were divided into 4 groups (n = 8): group I (control), group II: ischemia-reperfusion (30 minutes ischemia and 120 minutes reperfusion), group III: ischemia-reperfusion+uridine (at the beginning of reperfusion), and group IV: ischemia-reperfusion+uridine (5 minutes before ischemia-reperfusion). Uridine was administered a single dose of 30 mg/kg IV. The 3 elements of the hepatoduodenal ligament (hepatic artery, portal vein, and biliary tract) were obliterated for 30 minutes. Then hepatic reperfusion was achieved for 120 minutes. Results: In the ischemia-reperfusion group, both liver tissues and serum chymase activity and high-temperature requirement A2 levels were higher. Severe central vein dilatation and congestion, widening sinusoidal range, diffuse necrotic hepatocytes and dense erythrocyte accumulation in sinusoids, and strongly inducible nitric oxide synthase expression were seen in the ischemia-reperfusion group. A clear improvement was seen in both uridine co-administration and pretreatment groups. Conclusion: Our results revealed that uridine limits the development of liver damage under conditions of ischemia-reperfusion, thus contributing to an increase in hepatocyte viability Cite this article as: Koc S, Dogan HO, Karatas O, Erdogan MM, Polat V. Mitochondrial homeostasis and mast cells in experimental hepatic ischemia-reperfusion injury of rats. Turk J Gastroenterol. 2022;33(9):777-784.